A starch- and sucrose-reduced diet leads to a more favorable nutrient profile than low FODMAP in patients with irritable bowel syndrome. A randomized clinical trial - Al-Shiblawi, Noor; Cullman, Kristina; Roth, Bodil; Liljebo, Therese; Störsrud, Stine; Ohlsson, Bodil (Human Nutrition and Metabolism, 2025)
A diet low in fermentable oligo-, di-, and monosaccharides and polyols (FODMAP) and a starch- and sucrose-reduced diet (SSRD) both alleviate symptoms in IBS. Our hypothesis was that restrictive diets may preserve good nutritional supply. The aims of the study were to compare nutritional intake between SSRD and low FODMAP, and correlations between changes in nutrient intake, weight, and symptoms. This open, non-inferiority trial included patients with IBS according to Rome IV for a 4-week dietary intervention. Patients completed a 3-day food diary, study questionnaire, Rome IV questionnaire, IBS-severity scoring system (IBS-SSS), and visual analog scale for IBS (VAS-IBS) at baseline, after 4 weeks of either SSRD or low FODMAP, and at a 6-month follow-up. Daily intake of nutrients was calculated. In total, 155 patients (84 % women), 42 (32–55) years, weight 69.2 (63.0–82.9) kg, were included; 77 randomized to SSRD and 78 to low FODMAP diet. After 4 weeks, both SSRD and low FODMAP reduced symptoms, weight, and intake of calories, carbohydrates, sucrose, and monosaccharides, while vitamin D and B12 intake were increased. SSRD uniquely reduced added sugar, disaccharides, starch, and sodium chloride intake, while increasing protein, fat, vitamins, and minerals. In contrast, low FODMAP reduced intakes in fiber and several vitamins and minerals after 4 weeks and follow-up. The reductions of galacto-oligosaccharides and fructan were most pronounced in SSRD (p < 0.001). These findings highlight the SSRD's potential for broader health benefits and a more nutritionally balanced approach with higher nutrient density compared to the low FODMAP diet.
Keywords: Dietary intervention; Irritable bowel syndrome; Low FODMAP diet; Macronutrients; Micronutrients; Starch- and sucrose-reduced diet